INFORMATION NEEDED WHILE USING ICTS AMONG MAIZE FARMERS IN DANGBO AND ADJOHOUN FARMERS IN SOUTHERN BENIN REPUBLIC - KPAVODE, Aboua Yven Gérald; Vissoh, V. Pièrre (My University, 2020)
This study assessed Information needed while using ICTs among maize farmers in Dangbo and Adjohoun in southern Benin Republic. Data were collected from a random sample of 150 maize farmers. The data collected were analysed using descriptive statistics and inferential statistics used were Chi-square, Pearson’s Product Moment Correlation and t-test at p=0.05. The results showed that farmers’ mean age was 43}1 years and were mostly male (88.0 %), married (88.0 %), Christians (67.3%) and 48.7% had no formal education. Prominent constraints to ICTs use were power supply (_ =1.80) and high cost of maintenance of ICTs gadget (_ =1.58).The most needed information by farmers using ICTs was on availability and cost of fertilisers insecticides and herbicides (_ =1.20) and availability and cost of labour (_ =1.16). Farmers’ constraints (t=2.832; p=0.005) significantly differed between Dangbo and Adjohoun communes. The information need of farmers in Dangbo and Adjohoun communes (t=0.753; p=0.453) do not significantly differ. The study concluded that the major barriers facing ICTs usage were power supply and high cost of maintenance of ICTs gadget; and there is the need for information on agricultural inputs. The study therefore recommended that government agencies in charge of power supply should make effort to ensure steady power supply.
Keywords: ICTs; Information need; Constraint; Maize production; Farmers